Complete Model of Mosque-based ZISWAF Sustainable Management - Nurhasanah, Neneng; Ikhwanuddin, Nandang; Saripudin, Udin; Rahman, M Ridha Taufik; Fathurrahman, M Rifqi; Fadhillah, Salma Nurul (KnE Social Sciences, 2024)
This study was conducted based on the cluster foundations of the ZISWAF Managing Organization, namely governmental organization, religious-based society organization, community-based society, Pashantren-based organization, Sharia-based financial institution, and campus-based organization. This study used qualitative research approach and descriptive analysis to analyze and describe the mosque-based ZISWAF sustainable management model in Jogokariyan mosque more deeply and systematically. The data consisted of primary data sources such as the results of interviews, FGD, and observations, as well as secondary and tertiary data, such as books, journals, and the website of Jogokariyan Mosque. The results showed that the comprehensive ZISWAF sustainable management model is based on the mosque: 1) The management philosophy is based on the practice of QS. 9:18 that the empowerment of Jamaah economy is an attempt to restore the function of the mosque in the apostolic times, namely, as a place of worship, the building of the awareness and spirituality of Jamaah, the economic development and the solution to various problems of society with the community’s jargon. 2) In empowerment, all Jamaah layers (children, adolescents, mosque alumni, young couples, mothers, and parents) are included and their programs are adapted to their respective interests, talents, and tendencies. 3) In ZISWAF’s assembly there are several models namely: (1) infiradi models (individual or institutional) and jama’i (general society), and (2) conventional and creative-innovative models. In terms of empowerment, it was organized by 30 managerial units under the direction of Jogokariyan Mosque in the spiritual, educational, economic, entrepreneurial, health, and other sectors. Keywords: management model, sustainable, productive ZISWAF, mosque